2016
DOI: 10.1074/jbc.m115.703710
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a Domain of the Negative Regulator of the Ras-ERK Pathway, SPRED1 Protein, and the GTPase-activating Protein-related Domain of Neurofibromin Is Implicated in Legius Syndrome and Neurofibromatosis Type 1

Abstract: Constitutional heterozygous loss-of-function mutations in the SPRED1 gene cause a phenotype known as Legius syndrome, which consists of symptoms of multiple café-au-lait macules, axillary freckling, learning disabilities, and macrocephaly. Legius syndrome resembles a mild neurofibromatosis type 1 (NF1) phenotype. It has been demonstrated that SPRED1 functions as a negative regulator of the Ras-ERK pathway and interacts with neurofibromin, the NF1 gene product. However, the molecular details of this interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 39 publications
5
69
0
1
Order By: Relevance
“…Another study showed that overexpression of SPRED1 inhibits Ras activation, as evidenced by decreased levels of GTP-bound Ras (5, 8). Consistent with this last model, SPRED1 was reported to reduce GTP-Ras levels and MAPK signaling by corecruiting neurofibromin (NF1), a Ras-inactivating and GTPase-activating protein (GAP), to the plasma membrane (5,(8)(9)(10).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Another study showed that overexpression of SPRED1 inhibits Ras activation, as evidenced by decreased levels of GTP-bound Ras (5, 8). Consistent with this last model, SPRED1 was reported to reduce GTP-Ras levels and MAPK signaling by corecruiting neurofibromin (NF1), a Ras-inactivating and GTPase-activating protein (GAP), to the plasma membrane (5,(8)(9)(10).…”
mentioning
confidence: 58%
“…Our new mechanism does not exclude the possibility that the GTPase-activating protein (GAP) NF1 is in addition recruited to the membrane together with SPRED1, as suggested before (9,10). NF1 recruitment may then in addition deactivate Ras.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…SPRED1 acts as a tumor suppressor because it enhances NF1 inhibitory activity by recruiting the protein to the plasma membrane and to RAS (Stowe et al, 2012; Hirata et al, 2016) (Figure 1). Mutations in SPRED1 act in an autosomal-dominant manner in Legius and Neurofibromatosis 1-like (NF1-like) syndromes, mild forms of neurofibromatosis type 1 carrying skin features such as multiple café-au-lait macules, but no neurofibromas (Brems et al, 2012).…”
Section: Comparisons Of Specific Genesmentioning
confidence: 99%
“…37 A SL poderá associar-se a um risco aumentado de neoplasias, estando descritos casos de leucemia mieloblástica aguda em crianças com SL. 38 Esta associação deve-se ao papel do gene SPRED1 na regulação da hematopoiese, por intermédio da inibição da proteína ERK. A ausência de atividade da proteína Spred-1 provoca uma hiperatividade da via RAS/MAPK.…”
Section: Síndrome De Legiusunclassified